Interaction Between Non-Coding RNAs and Interferons: With an Especial Focus on Type I Interferons - Ghafouri-Fard, Soudeh; Poornajaf, Yadollah; Dashti, Farzaneh; Hussen, Bashdar Mahmud; Taheri, Mohammad; Jamali, Elena (Frontiers in Immunology, 2022)
Interferons (IFNs) are a group of cellular proteins with critical roles in regulation of immune responses in the course of microbial infections. Moreover, expressions of IFNs are dysregulated in autoimmune disorders. IFNs are also a part of immune responses in malignant conditions. Expression of these proteins and activities of related signaling can be influenced by a number of non-coding RNAs. IFN regulatory factors (IRFs) are the most investigated molecules in the field of effects of non-coding RNAs on IFN signaling. These interactions have been best assessed in the context of cancer, revealing the importance of immune function in the pathoetiology of cancer. In addition, IFN-related non-coding RNAs may contribute in the pathogenesis of neuropsychiatric conditions, systemic sclerosis, Newcastle disease, Sjögren’s syndrome, traumatic brain injury, lupus nephritis, systemic lupus erythematosus, diabetes mellitus and myocardial ischemia/reperfusion injury. In the current review, we describe the role of microRNAs and long non-coding RNAs in the regulation of IFN signaling.